2020
DOI: 10.1108/medar-09-2019-0566
|View full text |Cite
|
Sign up to set email alerts
|

The use of social media as a legitimation tool for sustainability reporting

Abstract: Purpose This paper aims to examine the use of social media for sustainability reporting by the largest Australia companies as a means of seeking legitimacy from stakeholders. Design/methodology/approach Qualitative content analysis was applied to examine social and environmental disclosures posted by Australian companies on three social media platforms – Facebook, Twitter and LinkedIn, and to observe stakeholder interaction in relation to the social and environmental postings. Findings The findings of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 52 publications
(94 reference statements)
1
32
0
1
Order By: Relevance
“…Considering the growing request for transparency and accountability, scholars have begun to investigate alternative reporting channels. Websites have emerged as a more useful tool for improving disclosure to stakeholders (Douglas et al, 2004;Lodhia et al, 2020;Manes-Rossi et al, 2018;Nicol o et al, 2020a, b).…”
Section: Prior Research On Csr Disclosure Onlinementioning
confidence: 99%
See 4 more Smart Citations
“…Considering the growing request for transparency and accountability, scholars have begun to investigate alternative reporting channels. Websites have emerged as a more useful tool for improving disclosure to stakeholders (Douglas et al, 2004;Lodhia et al, 2020;Manes-Rossi et al, 2018;Nicol o et al, 2020a, b).…”
Section: Prior Research On Csr Disclosure Onlinementioning
confidence: 99%
“…The literature on website-based corporate disclosure has demonstrated that these channels provide more flexibility, lower costs, timeliness and speed regarding CSR communication (Rodriguez-Bolivar et al, 2013). Moreover, Lodhia et al (2020) have highlighted that social media has changed reporting dynamics, incorporating dialogue and engagement with stakeholders to seek legitimacy. In keeping with these arguments, several scholars have investigated CSR disclosure through websites in different sectors (Table 1): universities (e.g.…”
Section: Corporate Social Responsibility In Wineriesmentioning
confidence: 99%
See 3 more Smart Citations